Estimation of fatigue lifetime for selected metallic materials under multiaxial variable amplitude loading (Fracture and Structural Integrity, 2016)
This paper initially investigates the accuracy of two methods, i.e., the Maximum Variance Method (MVM) and the Maximum Damage Method (MDM), in predicting the orientation of the crack initiation plane in three different metallic materials subjected to multiaxial variable amplitude loading. According to the validation exercise being performed, the use of both the MVM and the MDM resulted in a satisfactory level of accuracy for selected three metals. Subsequently, three procedures to estimate the fatigue lifetime of metals undergoing multiaxial variable amplitude loading were assessed quantitatively. Procedure A was based on the MDM applied along with Fatemi-Socie’s (FS) criterion, Bannantine-Socie’s (BS) cycle counting method and Miner’s linear rule. Procedure B was based on the MVM, FS criterion, BS cycle counting method and Miner’s linear rule. Procedure C involved the MVM, the Modified Manson Coffin Curve Method (MMCCM), the classical rainflow cycle counting method and Miner’s linear rule. The results show that the usage of these three design procedures resulted in satisfactory predictions for the materials being considered, with estimates falling within an error band of three.
Keywords: Multiaxial fatigue; Variable amplitude loading; Critical plane; Life prediction